Oxytocin: co-evolution of human and domesticated animals - Yu. E. Herbeck; R. G. Gulevich; D. V. Shepeleva; V. V. Grinevich (Вавиловский журнал генетики и селекции)
The neuropeptide oxytocin (OT) and its homologues are produced in specialized neurons located in Vertebrates exclusively in a deep and evolutionarily old part of the forebrain, the hypothalamus. The axons of OT neurons form the classical hypothalamic-neurohypophyseal tract terminating on blood vessels of the neurohypothysis to release OT into the systemic blood circulation. However, as was recently demonstrated in mammals, collaterals of OT axons concomitantly project to various forebrain regions to modulate the activity of local networks. At the behavioral level, OT facilitates intraspecific social contacts in mammals via various mechanisms ranging from the suppression of neuroendocrine stress responses to the direct OT action on neurons of socially relevant brain regions. Recent reports indicated possible contribution of OT to the formation of the social bond between domesticated mammals (dog, sheep, cattle) and humans. Indeed, social interaction between humans and a domesticated animal resulted in the elevation of peripheral OT levels (in blood, saliva or urine) and, in congruence, exogenous (intranasal) OT application led to more frequent contacts between the owner and the domesticated animal. It has been known for decades that domesticated animals exhibit profound socio-communicative abilities accompanied by suppressed aggression and stress responsiveness. These peculiarities of their behavior and physiology may be influenced by the activity of the central OT system. Therefore, in the present mini-review we focus on the role of OT in the orchestration of distinct forms of social behavior, including the monogamous bond, maternal care, social memory and recognition, aggression, and anxiety. As a conclusion, we propose possible directions for exploration of the OT contribution to empathy between humans and domesticated animals, which was likely established in the course of their co-evolution during last 10.000– 15.000 years.